An Evaluation of Kiso Moji Goi Course Learning - Soni Mulyawan Setiana (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
This study aims to obtain an overview of the results of the evaluation of the implementation of learning which includes methods, materials, media, academic services, and assessing learning outcomes of Basic Japanese Characters and Vocabulary faced by students. This study uses descriptive quantitative research methods, using several research techniques in the form of questionnaires, interviews, and document analysis. Respondents in this study were 45 first-level students of the Japanese Department, Faculty of Humanities, Universitas Komputer Indonesia in the 2021/2022 academic year. The results showed that 82.2% of students stated that they were satisfied with the learning method applied by the lecturer, 51.5% of students stated that the level of material difficulty was in the medium category, 88.9% of students stated that the learning media used by the lecturer was good, 84.4% of students stated that the test used by the lecturer was good carried out according to the material that has been taught, 88.9% of students are satisfied with the academic services provided by the lecturer, 93.4% of students got a good final grade. Therefore, based on the results of the evaluation that has been carried out, it can be concluded that the quality of the implementation of Kiso Moji Goi learning is good. Efforts to improve student learning outcomes, such as by increasing the quantity of the use of project-based learning and problem-based learning methods, are needed.